2015
DOI: 10.1002/humu.22747
|View full text |Cite
|
Sign up to set email alerts
|

Gene Conversion Between Cationic Trypsinogen (PRSS1 ) and the Pseudogene Trypsinogen 6 (PRSS3P2 ) in Patients with Chronic Pancreatitis

Abstract: Mutations of the human cationic trypsinogen gene (PRSS1) are frequently found in association with hereditary pancreatitis. The most frequent variants p.N29I and p.R122H are recognized as disease-causing mutations. Three pseudogene paralogs in the human trypsinogen family, including trypsinogen 6 (PRSS3P2), carry sequence variations in exon 3 which mimic the p.R122H mutation. In routine genetic testing of patients with chronic pancreatitis we identified in two unrelated individuals similar gene conversion event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…DNA exchange by gene conversion is of paramount importance for the evolution of gene families but it can also cause human diseases [18] including CP and other pancreatic pathologies. Gene conversion events between PRSS1 and PRSS2 or between PRSS1 and the pseudogene PRSS3P2 were shown to generate pathogenic alleles that cause hereditary pancreatitis [19,20,21]. More recently, a recombination allele of the carboxyl ester lipase gene ( CEL ) and its pseudogene CELP was described as a novel genetic risk factor for CP [22].…”
Section: Discussionmentioning
confidence: 99%
“…DNA exchange by gene conversion is of paramount importance for the evolution of gene families but it can also cause human diseases [18] including CP and other pancreatic pathologies. Gene conversion events between PRSS1 and PRSS2 or between PRSS1 and the pseudogene PRSS3P2 were shown to generate pathogenic alleles that cause hereditary pancreatitis [19,20,21]. More recently, a recombination allele of the carboxyl ester lipase gene ( CEL ) and its pseudogene CELP was described as a novel genetic risk factor for CP [22].…”
Section: Discussionmentioning
confidence: 99%
“…Two highlighted the importance of specific promoter variants in SPINK1 (8), and chymotrypsin C (CTRC) as a risk factor for CP. (9) Another reported on the importance of gene conversion events leading to phenotypes similar to established genetic mutation variants in PRSS1 (10). A validation genome wide association study (GWAS) of CP confirmed a protective effect of a PRSS1-PRSS2 SNP, and an increased risk in variants of the CLDN2-MORC2 loci in alcoholic CP.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In PRSS1 hybrid alleles such as PRSS1-PRSS2 [66] and PRSS1-PRSS3P2 [67] generated by gene conversion events, although rare, are causative mutations in chronic pancreatitis.…”
Section: Prss2mentioning
confidence: 99%